Feminisms in the University. Mapping Interruptions from/at the Faculty of Social Sciences/UNC - Scarpino, Pascual (2024)
This paper presents the results of a diagnostic research on the implementation of the Feminist Institutional Policy (PIF) developed within the framework of the Faculty of Social Sciences of the National University of Cordoba, Argentina. With the aim of understanding the state of affairs, a rigorous documentary review and the analysis of sixteen semi-structured interviews with key informants were carried out. This article organizes the findings around the state of implementation and dynamics of PIF in three dimensions: what has been written, what has been said and what has been done on the issue in question. In each of these dimensions, the results of documentary mapping and narrative analysis are brought together. Finally, three considerations derived from the research are highlighted: the polysemy surrounding feminist institutional politics, the ruptures generated by the assumption of such a commitment in the institutional dynamics, and the daily rehearsal as an ethic of feminist action.